NEUROANATOMI DAN APLIKASI PEMBELAJARAN ANAK USIA DINI - Chofsatun; Miftah Lilik Nur Aziza; Wiwik Jumiati (STPI Bina Insan Mulia Yogyakarta, 2019)
Neuroscience is a field of study regarding the nervous system in the human brain. Neuroscience is a new educational system that studies the nervous system. Educators generally rarely pay attention to this problem, resulting in a debate between the two sides of the brain-mind, soul-body, mind-heart. Therefore, education needs to incorporate neuroscience into learning practitioners. The purpose of making this paper is to determine the 3 types of intelligence in humans divided into 3 parts, namely: Intellectual intelligence or IQ (Intelligence quotient), Emotional Intelligence or EQ (Emotional quotient) and Spiritual Intelligence or SQ (Spiritual quotient). The method used in this paper is data collection techniques qualitative research techniques